A Lexical-Pragmatic Approach to Japanese Wakamono Kotoba ‘Youth Language’ yabai - Li, Wenchao (International Journal of Linguistics, 2021)
This study uncovers the morphosyntactic properties of yabai and its clipped forms. It aims to arrive at an understanding of how the forms and the meanings might be associated. A lexical-pragmatic-based analysis was carried out using Twitter and speech corpus data. The findings reveal the following picture of the lexeme: (a) when yabai undertakes an adjective role, modifying a noun, it is likely that a negative evaluation is invited. In this regard, yabai fulfils a lexical function. (b) The adverb use of yabai presents two variations: modifying a verb or modifying an i-adjective. At any rate, the adverb use describes the degree of an event or an object, leading to the assumption that yabai fulfils a grammatical function. (c) The predicate function presents the following diversities: the negative-denotation yabai and yabee are lexical items; the positive/neutral-denotation yabai, yabee and yaba are grammatical items. The clipped forms, i.e. yaba; yabee and yabe are limited to interjection use and adverb use, which are signs of complete grammaticalisation. A quantitative analysis via KH Coder suggests that yabai’s adverb function appears to be limited to women friendships, with parent-child relationship and vertical relationship being ruled out.